The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/jitc-2020-001806
|View full text |Cite|
|
Sign up to set email alerts
|

KEYNOTE-022 part 3: a randomized, double-blind, phase 2 study of pembrolizumab, dabrafenib, and trametinib in BRAF-mutant melanoma

Abstract: BackgroundIn the KEYNOTE-022 study, pembrolizumab with dabrafenib and trametinib (triplet) improved progression-free survival (PFS) versus placebo with dabrafenib and trametinib (doublet) without reaching statistical significance. Mature results on PFS, duration of response (DOR), and overall survival (OS) are reported.MethodsThe double-blind, phase 2 part of KEYNOTE-022 enrolled patients with previously untreated BRAFV600E/K-mutated advanced melanoma from 22 sites in seven countries. Patients were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 27 publications
4
140
0
2
Order By: Relevance
“…It could not meet its primary endpoint of improved median PFS, although a trend to a longer PFS with pembrolizumab (median PFS 16.0 months compared to 10.3 months with placebo) was reported. An updated analysis of KEYNOTE 022 at 24-month follow-up showed the triplet potential as a treatment option for patients with BRAF -mutant advanced melanoma ( 90 ). 24-month PFS rates were 41% with pembrolizumab versus 16.3% with placebo; mOS was not reached with pembrolizumab versus 26.3 months with placebo (HR: 0.64; 95% CI: 0.38–1.06).…”
Section: Treatment Of Stage Iii/iv Non-resectable Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…It could not meet its primary endpoint of improved median PFS, although a trend to a longer PFS with pembrolizumab (median PFS 16.0 months compared to 10.3 months with placebo) was reported. An updated analysis of KEYNOTE 022 at 24-month follow-up showed the triplet potential as a treatment option for patients with BRAF -mutant advanced melanoma ( 90 ). 24-month PFS rates were 41% with pembrolizumab versus 16.3% with placebo; mOS was not reached with pembrolizumab versus 26.3 months with placebo (HR: 0.64; 95% CI: 0.38–1.06).…”
Section: Treatment Of Stage Iii/iv Non-resectable Melanomamentioning
confidence: 99%
“…G3–5 AEs occurred in 58.3% of the pembrolizumab group versus 25% of the placebo group. The most common G3–5 trAEs were pyrexia (10.0% versus 3.3%), increased aspartate aminotransferase (6.7% versus 3.3%), and increased γ-glutamyl transferase (6.7% versus 5.0%) ( 90 ).…”
Section: Treatment Of Stage Iii/iv Non-resectable Melanomamentioning
confidence: 99%
“…Tx-related adverse events (TRAEs) grade ≥ 3 occurred in 55% vs 33% of pts treated with spartalizumb arm versus placebo. TRAEs leading to discontinuation of all 3 study drugs occurred in 12% vs 8% of pts in the two arms, respectively [37].…”
Section: Discussionmentioning
confidence: 94%
“…Screening of the full-text citations resulted in the exclusion of studies that did not fulfill the inclusion criteria (n=14); did not show adequate data (n=7); not randomized clinical studies (n=1) or in the early stage of clinical trials without uploaded results (n=15). Finally, five randomized clinical trials (RCTs) were included in our meta-analysis (20,21,(24)(25)(26))and details about selection of studies were schematically shown in Figure 1.…”
Section: Included Trials and Studiesmentioning
confidence: 99%